2019
DOI: 10.4103/jmh.jmh_154_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of poor functional status and its predictors among the elderly in a rural area of West Bengal

Abstract: Context:Functional ability considered a proxy for healthy aging, not only related to mental and physical health but it also determines social well-being. Eliciting the determinants of functionality components among the elderly will assist in evolving with appropriate plans at both domiciliary and facility level to eliminate their sufferings and disabilities.Aim:The aim of this study is to find out the magnitude of poor functional status among the elderly and its predictors.Materials and Methods:This is a commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
3
10
1
1
Order By: Relevance
“…Our study suggests that age was a significant predictor of IADL score, which agrees with previous findings [ 13 , 41 ]. Aging is associated with generalized deterioration of body organs and systems, lowering effectiveness of physiological functions, which lead to a greater risk for various chronic disease and inadaptability among elderly.…”
Section: Discussionsupporting
confidence: 93%
“…Our study suggests that age was a significant predictor of IADL score, which agrees with previous findings [ 13 , 41 ]. Aging is associated with generalized deterioration of body organs and systems, lowering effectiveness of physiological functions, which lead to a greater risk for various chronic disease and inadaptability among elderly.…”
Section: Discussionsupporting
confidence: 93%
“…Female elderly were more likely to have the risk of ADL and IADL limitation than male elderly. Previous studies are in line with the nding of this study [1,[27][28][29][30]. Studies worldwide have also shown that the female gender is one of the risk factors for disability in old age [31][32].…”
Section: Discussionsupporting
confidence: 90%
“…Studies worldwide have also shown that the female gender is one of the risk factors for disability in old age [31][32]. Female elderly are still neglected in terms of care with a minuscule focus on their health; it is due to gendersegregated behavioural activities in our society that makes female more vulnerable than male [30]. Researchers feel that gender discrimination in a male-dominated society like India makes females more vulnerable to the risk of disabilities [29].…”
Section: Discussionmentioning
confidence: 99%
“…Female elderly were more likely to have the risk of ADL limitation than male elderly, in the present research, which was supported by prior research. [ 9 20 21 ] Gender inequality makes females more vulnerable to the danger of being disabled in a male-dominated society like India. Further, Indian females are more inclined to overlook their health and do not seek suitable medical attention at the right time.…”
Section: Discussionmentioning
confidence: 99%